2016
DOI: 10.1016/j.apcatb.2015.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Surface Ba species effective for photoassisted NO storage over Ba-modified TiO2 photocatalysts

Abstract: HighlightsBa-modified TiO 2 photocatalysts showed high activity in photoassisted NO x storage.Modification of TiO 2 photocatalysts with Ba enhanced the photocatalytic activity.Ba loading had an significant effect on the photocatalytic activity.Ba-Ti mixed oxides were formed on a TiO 2 surface after O 2 pretreatment at 773 K.The generated Ba-Ti mixed oxides function as an effective NO x storage material.ABSTRACT Surface modification of a TiO 2 photocatalyst with Ba species was investigated in photoassisted nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…According to the equation shown in section , the NO 2 selectivity of P25 was only 12.2%, which is twice that of STO (6.3%), suggesting that STO is more advantageous in realistic conditions. Previous studies showed that barium oxide (BaO) species could function as NO x storage material to promote the photocatalytic activity of TiO 2 . , Thus, it is assumed that Sr–O in STO matrix would have the similar behavior that promotes NO x adsorption and avoids the release of NO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the equation shown in section , the NO 2 selectivity of P25 was only 12.2%, which is twice that of STO (6.3%), suggesting that STO is more advantageous in realistic conditions. Previous studies showed that barium oxide (BaO) species could function as NO x storage material to promote the photocatalytic activity of TiO 2 . , Thus, it is assumed that Sr–O in STO matrix would have the similar behavior that promotes NO x adsorption and avoids the release of NO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Perovskites are widely studied as catalysts for SCR processes, , whereas the potential ability as photocatalysts for NO x abatement is rarely focused. As an important n -type perovskite semiconductor, strontium titanate (SrTiO 3 ) has attracted lots of attention in solar H 2 production and energy conversion applications over the past years. One of the great advantages of SrTiO 3 , in comparison with TiO 2 , is the higher conduction band position (−1.4 V vs SCE at pH 13) that drives more efficient charge transfer to electron acceptor (e.g., O 2 ), leading to enhanced photocatalytic efficiencies. , Moreover, it is expected that with the presence of strontium sites, the interaction between NO molecule and the photocatalyst would change, possibly promoting the complete conversion of NO . Nevertheless, SrTiO 3 can only be excited by light with shorter wavelength, owing to its wide band gap energy of 3.2 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here in this work, we adopted the latter approach to construct hierarchical LaFeO 3 -SrTiO 3 composite for photocatalytic NO abatement. SrTiO 3 was chosen firstly because it has similar crystal structure with LaFeO 3 ; secondly, SrTiO 3 with surface basic sites is advantageous for NO x adsorption and conversion [23]; and thirdly, their band edge differences might be facilitating the interfacial charge transfer. To the best of our knowledge, this is the first time to report perovskite LaFeO 3 -SrTiO 3 composites and their functional use as photocatalysts to remove NO at ppb level.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that the incorporation of Ti cations at B sites and Nd cations at A sites resulted in the enhanced conductivity of pyrochlore-phase Gd 2 Zr 2 O 7 in the temperature range of 773–973 K 27, 28 . In this work, we studied firstly the incorporation of alkaline earth metals (Ca, Sr, and Ba) in pyrochlore-phase Gd 2 Zr 2 O 7 based on the following two core considerations: (1) Incorporation of alkaline earth metals creates more amounts of oxygen vacancy into the solid electrolyte and increases oxygen migration to facilitate the anodic reaction; (2) Alkaline earth metals serves as a dopant in view of its strong NO 2 storage capacity required for the electrochemical catalytic performance at low and moderate temperatures 2932 , which is in favor of the enrichment of NO 2 at the interface between SE and solid electrolyte, consequently active for NO 2 sensing. And then we fabricated several amperometric-type NO 2 sensors based on the alkaline earth metals doped pyrochlore Gd 2 Zr 2 O 7 oxygen conductors with NiO as the SE and a noble metal Pt as the RE.…”
Section: Introductionmentioning
confidence: 99%